1984
DOI: 10.1111/j.1365-2133.1984.tb04698.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential fatty acids in the plasma phospholipids of patients with atopic eczema

Abstract: We have measured all the essential fatty acids (EFA) in plasma phospholipids in forty-one adults with atopic eczema and fifty normal controls. The major dietary n-6 EFA, linoleic acid, was significantly elevated, but all its metabolites, 18:3n-6, 20:3n-6, 20:4n-6, 22:4n-6, and 22:5n-6 were significantly reduced. The major dietary n-3 EFA, alpha-linolenic acid, was also elevated, though not significantly, while all its metabolites were also significantly reduced. These observations suggest that atopic eczema is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
1
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(86 citation statements)
references
References 4 publications
8
76
1
1
Order By: Relevance
“…A first motive of interest attests that our results give credit to the hypothesis already drawn out by additional studies, of an enzyme deficit regarding the delta-6-desaturase, the first enzyme of the sequence forming AGL by adding a double link to LA [30]. We could also hypothesize a reduced ADGL production and then of PGE-1.…”
Section: Discussionsupporting
confidence: 52%
“…A first motive of interest attests that our results give credit to the hypothesis already drawn out by additional studies, of an enzyme deficit regarding the delta-6-desaturase, the first enzyme of the sequence forming AGL by adding a double link to LA [30]. We could also hypothesize a reduced ADGL production and then of PGE-1.…”
Section: Discussionsupporting
confidence: 52%
“…This has been corroborated for the ω–6 and the ω–3 series by some [3, 4], but not all other studies [5]. The clinical significance of these findings is controversial, however, since some randomised, placebo–controlled double–blind studies have shown a clinical improvement in patients with atopic eczema after treatment with Epogam, a GLA–rich oil from Evening primrose [6], while in other studies there was no effect of such treatment [7].…”
Section: Introductionsupporting
confidence: 66%
“…Adult patients with atopic eczema were compared with normal individuals with regards to the fatty acid composition of plasma phospholipids [47]. Linoleic acid (LA) concentration was slightly above normal while its metabolites GLA, dihomo-γ-linolenic acid (DGLA 20:3n-6) and arachidonic acid were below normal.…”
Section: Atopic Eczema and Psoriasismentioning
confidence: 99%